2018
DOI: 10.1038/s41598-018-33483-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Safety of Dipeptidyl Peptidase-4 Inhibitors Versus Sulfonylureas and Other Glucose-lowering Therapies for Three Acute Outcomes

Abstract: Although the glucose lowering effect of dipeptidyl peptidase-4 (DPP4) inhibitors is well established, several potential serious acute safety concerns have been raised including acute kidney injury, respiratory tract infections, and acute pancreatitis. Using the UK-based Clinical Practice Research Datalink (CPRD), we identified initiators (365-day washout period) of DPP4 inhibitors and relevant comparators including initiators of sulfonylureas, metformin, thiazolidinediones, and insulin between January 2007 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
(45 reference statements)
2
12
0
Order By: Relevance
“…Evidence from ongoing trials and continued pharmacovigilance will provide further insights into the long-term pancreatic safety of this drug class. The safety findings of CARMELINA are consistent with findings observed for the DPP-4 inhibitor class as a whole; these agents have been shown to be well tolerated with a favorable safety profile, including a low risk of hypoglycemia [7,24,25].…”
Section: Resultssupporting
confidence: 65%
“…Evidence from ongoing trials and continued pharmacovigilance will provide further insights into the long-term pancreatic safety of this drug class. The safety findings of CARMELINA are consistent with findings observed for the DPP-4 inhibitor class as a whole; these agents have been shown to be well tolerated with a favorable safety profile, including a low risk of hypoglycemia [7,24,25].…”
Section: Resultssupporting
confidence: 65%
“…Although there was an initial report of increase in nasopharyngitis with the DPP-4Is during the phase 3 clinical development program, however, the later larger trials with their meta-analysis and the longer cardiovascular outcome trials (CVOTs) with these class did not show any such signals. Similarly, the UK-based Clinical Practice Research Datalink (CPRD) database that studied 103,159 patients of diabetes over 8-years that compared the respiratory tract infection with DPP-4Is to SUs, metformin, TZD and insulin, found no significant increase in risk [65]. These findings were further reassured by few studies conducted in immunocompromised patients with human immunodeficiency virus (HIV), showing no increase in infection with the DPP-4Is [66].…”
Section: Dpp-4 Inhibitorsmentioning
confidence: 97%
“…It has been previously demonstrated that both CD8(+)CD26(high) and CD8(+)CD26(−) cells represent activated cell phenotypes and may offer a characteristic marker of successful memory development (Hatano, Ohnuma, Yamamoto, Dang, & Morimoto, 2013;Ibegbu et al, 2009). CD28 is one of the molecules expressed in T cells, which provides co-stimulatory signals for T cell activation (Gamble et al, 2018). Interestingly, CD26-mediated co-stimulation of CD8(+) T cells results in greater cytotoxic effect than that induced by CD28 co-stimulation pathway (Hatano et al, 2013).…”
Section: Cd4(+) and Cd8(+) T Cellsmentioning
confidence: 99%
“…Increased risk of nasopharyngitis and urinary tract infection but no association of upper respiratory tract infections in T2DM patients (Amori et al, 2007;Gamble et al, 2018) Potential adverse effect on MERS patients (Inn et al, 2018;Raj et al, 2013) Potential therapeutic effect on HCV patients (Decalf et al, 2016;Riva et al, 2014) No effect on HIV patients (Dube et al, 2019;Goodwin et al, 2013)…”
Section: Infectious Diseasesmentioning
confidence: 99%
See 1 more Smart Citation